PEMERIKSAAN STIMULASI DETEKSI INTERVENSI DINI TUMBUH KEMBANG (SDIDTK) ANAK BALITA DI PAUD DAN KOBER MUSLIM CENDIKIA - Esa Risi Suazini; Lina Humaeroh; Fitri Hanriyani; Rosita Alvia; Anita Nurjanah; Pepi (Jurnal Pengabdian Masyarakat DEDIKASI, 2020)
Quality humans are formed from infancy. Quality of humans are humans who experience optimal growth and development, both physically, mentally, emotionally, psychosocially and spiritually. The purpose of this community service is to stimulate, detect and intervene early on growth and development in children to know the growth and development of children and help teachers and parents to always stimulate children's growth and development and detect and intervene early if growth problems occur. The method used was observation using a weight, head circumference and height measurement tool for 24 children. The results obtained from this activity Comparison of weight and height. The proportion of weight and height of students 24 children (100%) was normal, the results of the head circumference measurements of students, all showed normal and based on the results of measurements of child development, all showed normal results, there were no remainders that had to be referred. From the results of community service activities, it can be concluded from the proportion of weight and height of students, 1 child (4%) is in the very fat category, 10 children (42%) are in the obese category and 13 children (54%) are normal. The results of the students' head circumference measurements, all showed normal. And the results of child development, all showed normal results, there were no leftovers that had to be referred.